2000
DOI: 10.1007/s004220050601
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear analysis of continuous ECG during sleep II. Dynamical measures

Abstract: The hypothesis that cardiac rhythms are associated with chaotic dynamics implicating a healthy flexibility has motivated the investigation of continuous ECG with methods of nonlinear system theory. Sleep is known to be associated with modulations of the sympathetic and parasympathetic control of cardiac dynamics. Thus, the differentiation of ECG signals recorded during different sleep stages can serve to determine the usefulness of nonlinear measures in discriminating ECG states in general. For this purpose th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…The increase of CRR values during deeper sleep stages indicates an increase in the similarity of the studied activity. These observations tie in with findings from other studies, where it has been shown that EEG complexity decreases as the sleep deepens and increases again during REM sleep [10], while ECG activity exhibits a similar decrease in complexity during deep sleep compared to REM sleep [16]. Our observations could also be related to changes in the frequency content of both signals during different sleep stages [17].…”
Section: Results Andsupporting
confidence: 90%
“…The increase of CRR values during deeper sleep stages indicates an increase in the similarity of the studied activity. These observations tie in with findings from other studies, where it has been shown that EEG complexity decreases as the sleep deepens and increases again during REM sleep [10], while ECG activity exhibits a similar decrease in complexity during deep sleep compared to REM sleep [16]. Our observations could also be related to changes in the frequency content of both signals during different sleep stages [17].…”
Section: Results Andsupporting
confidence: 90%
“…In conclusion consideration of the ®ndings obtained with the two approaches suggests that embedding dimensions of 6±8 may be regarded as suitable for the topologically proper reconstruction of continuous ECG signals. Based on this knowledge we chose an embedding dimension of 8 in part II of this project (Fell et al 2000), where we investigated how dierent nonlinear characteristics of continuous ECG (correlation dimension, largest Lyapunov exponent, Kolmogorov entropy, as well as several unstable periodic orbit measures) change with sleep stage.…”
Section: Discussionmentioning
confidence: 99%
“…reconstruction of the signal in a multidimensional space. The choice of the optimal embedding dimension is crucial for proper signal reconstruction and subsequent evaluation of nonlinear characteristics, which we performed in part II of this project (Fell et al 2000). Arti®cial crossing and folding of trajectories in phase space is known to occur in the presence of underembedding and leads to the distortion of phase space structures.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is difficult to recognize patients with abnormal nonlinear HRV because the nonlinear properties in HRV may be altered under some physiological conditions, and the alterations may be of a sufficient magnitude to confound the so-called alterations derived from diseases. Previous studies have pointed out many physiological factors that affect nonlinear HRV properties, including age (6), gender (35), posture (67), and sleep (19), and so on. Here, we determined the influence of the menstrual cycle on the nonlinear properties of HRV.…”
Section: Correlations Between Nonlinear and Linear Hrv Measuresmentioning
confidence: 99%